Organized crimes violence related to economic sectors in Mexico. A categorizationproposal (Polis (Santiago), 2018)
Violence caused by organized crime has become one of the main problems in Mexico in recent years, in addition to causing human losses, affects economic activities which decreases the quality of life of the population. This paper presents a classification of violent behaviors performed by organized crime affecting economic sectors in Mexico, which was developed starting from a content analysis with the aid of MaxQDA software. The final classification consists of 17 behaviors which are described by identifying the government sector that is the most affected.
Keywords: violence; organized crime; economic sectors; content analysis